2000
DOI: 10.1212/wnl.54.9.1760
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of MRI measures of entorhinal cortex versus hippocampus in AD

Abstract: Despite the theoretical rationale for the superiority of entorhinal measurements in early AD, the authors found MRI measurements of the hippocampus and entorhinal cortex were approximately equivalent at intergroup discrimination. Measurements of the hippocampus may be preferable because MRI depiction of the boundaries of the entorhinal cortex can be obscured by anatomic ambiguity, image artifact, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
186
2
13

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(222 citation statements)
references
References 35 publications
21
186
2
13
Order By: Relevance
“…Although several studies examining cross-sectional and longitudinal effects in volumes of brain regions have shown significant group differences between MCI patients that convert to AD and MCI patients that don't convert, or between healthy controls and AD or MCI patients [2,8,9,[12][13][14][15][16]18,22,25,26,29,[31][32][33][34]36,44,46,50], the ability to detect structural patterns that enable accurate prediction for specific individuals is ultimately what determines the clinical value of MRI and measurements obtained from it. Our results further confirmed that evaluation of all these brain regions jointly is necessary to obtain high predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies examining cross-sectional and longitudinal effects in volumes of brain regions have shown significant group differences between MCI patients that convert to AD and MCI patients that don't convert, or between healthy controls and AD or MCI patients [2,8,9,[12][13][14][15][16]18,22,25,26,29,[31][32][33][34]36,44,46,50], the ability to detect structural patterns that enable accurate prediction for specific individuals is ultimately what determines the clinical value of MRI and measurements obtained from it. Our results further confirmed that evaluation of all these brain regions jointly is necessary to obtain high predictive accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further confirmed that evaluation of all these brain regions jointly is necessary to obtain high predictive accuracy. Measurements restricted to volumes of the hippocampus and ERC, two structures that are known to be affected early in AD [24] and show group differences in neuroimaging studies of AD and MCI [2,8,12,[14][15][16]18,26,29,32,36,44,50], provided considerably lower predictive accuracy. Lower accuracy was observed even when these measures were evaluated jointly, due to the high overlap of the volume distributions of these two structures between MCI and healthy individuals (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies examining cross-sectional and longitudinal effects in volumes of brain regions have shown significant group differences between AD or FTD and their respective healthy controls (DeLeon, George et al 1991;Cuenod, Denys et al 1993;Golomb, deLeon et al 1993;Killiany, Moss et al 1993;Lehericy, Baulac et al 1994;Laakso, Soininen et al 1995;Frisoni, Beltramello et al 1996;Convit, De Leon et al 1997;deToledo-Morrell, Sullivan et al 1997;Jack, Petersen et al 1997;Krasuski, Alexander et al 1998;Bobinski, de Leon et al 1999;Jack, Petersen et al 1999;Killiany, Gomez-Isla et al 2000;Laakso, Hallikainen et al 2000;Xu, Jack et al 2000;De Santi, de Leon et al 2001;Dickerson, Goncharova et al 2001;Du, Schuff et al 2001;Rosen, Prull et al 2003;Stoub, Bulgakova et al 2005), the ability to detect structural patterns that enable accurate prediction for specific individuals is ultimately what determines the clinical value of MRI and measurements obtained from it. Our results further confirmed that evaluation of an extensive and optimally determined set of brain regions, which collectively form a spatial pattern of brain atrophy, is necessary and sufficient to obtain high diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional MRI studies have shown that AD patients have significantly greater ERC and hippocampal atrophy than cognitively normal (CN) subjects [9,21,26,48,57]. Longitudinal MRI studies have suggested that the rates of ERC and hippocampal atrophy may be useful in predicting AD before the onset of clinical symptoms and in assessing the potential usefulness of pharmacological interventions in treatment trials [10,22,24,27,43].…”
Section: Introductionmentioning
confidence: 99%